From high friction zone to frontal collapse: dynamics of an ongoing tidewater glacier surge, Negribreen, Svalbard. Issue 259 (17th October 2020) - Haga, Odin Næss; McNabb, Robert; Nuth, Christopher; Altena, Bas; Schellenberger, Thomas; Kääb, Andreas
Abstract: Negribreen, a tidewater glacier located in central eastern Svalbard, began actively surging after it experienced an initial collapse in summer 2016. The surge resulted in horizontal surface velocities of more than 25 m d −1, making it one of the fastest-flowing glaciers in the archipelago. The last surge of Negribreen likely occurred in the 1930s, but due to a long quiescent phase, investigations of this glacier have been limited. As Negribreen is part of the Negribreen Glacier System, one of the largest glacier systems in Svalbard, investigating its current surge event provides important information on surge behaviour among tidewater glaciers within the region. Here, we demonstrate the surge development and discuss triggering mechanisms using time series of digital elevation models (1969–2018), surface velocities (1995–2018), crevasse patterns and glacier extents from various data sources. We find that the active surge results from a four-stage process. Stage 1 (quiescent phase) involves a long-term, gradual geometry change due to high subglacial friction towards the terminus. These changes allow the onset of Stage 2, an accelerating frontal destabilization, which ultimately results in the collapse (Stage 3) and active surge (Stage 4).